Inflammatory diseases in dairy cows: Risk factors and associations with pregnancy after embryo transfer - Edelhoff, I. N. F. [UNESP]; Pereira, M. H. C. [UNESP]; Bromfield, J. J.; Vasconcelos, J. L. M. [UNESP]; Santos, J. E. P. (Elsevier B.V., 2020)
The objectives of the present prospective cohort study were to identify risk factors for inflammatory diseases in Holstein-Gyr crossbred dairy cows and characterize the associations of those diseases with pregnancy per embryo transfer (ET). Diseases were diagnosed in the first 60 d postpartum in 252 primiparous and 481 multiparous cows. Uterine diseases (UTD) included retained placenta, metritis, clinical endometritis, and subclinical endornetritis. Nonuterine diseases (NUTD) included mastitis, lameness, pneumonia, and displaced abornasum. Blood was sampled on d 0, 1, and 2 postpartum and analyzed for concentrations of haptoglobin, fatty acids, total Ca (tCa), P, and Mg, and again on d 8 postpartum and analyzed for concentration of beta-hydroxybutyrate. The association between concentrations of metabolites in serum and inflammatory diseases was determined. Cows received a timed ET program starting 28 +/- 3 d postpartum with first ET at 46 +/- 3 d postpartum using fresh in vitro-produced embryos. Pregnancy was diagnosed on d 31 and 59 of presumptive gestation. Overall, 63.3% of the cows were diagnosed with UTD and 20.6% with NUTD. The risk factors for UTD included season of calving, parity group, calving problems, days with subclinical hypocalcernia, and serurri concentrations of haptoglobin and Mg, whereas the risk factors for NUTD were parity group and serum Mg concentration. Cows that developed UTD had increased concentrations of haptoglobin on d 2 arid fatty acids on d 1 and 2, arid reduced concentrations of tCa on d 1 and 2 and of P and Mg on d 2 postpartum compared with cows without UTD. Cows that developed NUTD had increased concentrations of fatty acids on d 0 to 2 postpartum, and decreased concentrations of tea and P on d 0 and 1, and of Mg on d 1 and 2 postpartum compared with cows without NUTD. Cows that developed NUTD had a 340-kg reduction in milk yield in the first 60 d postpartum. Inflammatory diseases were associated with lesser body condition score and increased loss of body condition in the first 70 d postpartum. Maintenance of pregnancy after ET was reduced in UTD cows following the first (41.7 vs. 25.4%) or all ET (46.4 vs. 36.2%), whereas maintenance of pregnancy was reduced in NUTD cows only at the second ET (39.0 vs 25.9%). The reduced pregnancy maintenance in UTD cows combined with a reduced 21-d service rate (61.9 vs. 54.8%) decreased the 21-d cycle pregnancy rate (28.6 vs. 19.9%) and the hazard of pregnancy to 300 d postpartum by 35%, resulting in an extra 32 d open. In conclusion, inflammatory diseases depressed fertility in dairy cows receiving ET, with the greatest impact observed in UTD cows. This suggests that local inflammation of the uterus impairs maintenance of pregnancy in dairy cows following ET.
Keywords: dairy cow; embryo transfer; inflammation; reproduction